Geochemistry of La Grande Riviere (L2T2C2-2) peat core from Canada - Michelle Garneau (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.